Community trial of silver fluoride treatment for deciduous dentition caries in remote Indigenous communities. (2nd April 2019) - Roberts‐Thomson, KF; Ha, DH; Wooley, S; Meihubers, S; Do, LG
Abstract: Background: Silver fluoride 40% followed by 10% stannous fluoride (AgF) has been used in dental practice in some parts of Australia for many years. This study compared the effectiveness of application of AgF with atraumatic restorative technique (ART) in managing cavitated carious primary molars. Methods: The study was a community effectiveness trial in two remote Aboriginal communities where AgF has been used for some time. Children between 4 and 8 years of age with caries on primary molars were randomized by birth date to receive AgF or ART. There were 210 children who were included in the study with 384 eligible teeth. Children were followed up for periods between 9 months and 4 years. Negative outcomes such as dental pain, extraction, use of antibiotics and more extensive restorative treatment were considered as the primary outcomes of the study. Results: Those negative outcomes were infrequent in both treatment groups. The prevalence ratio of negative sequelae for children treated with AgF compared with those treated with ART was lower at 0.18. Conclusions: Silver fluoride was well accepted, easy to use and at least as effective a treatment as ART for dental caries in primary molars in young Aboriginal children in remote areas.